Implementation of character education in islamic education - Maslani Maslani; Zen Anwar Saeful Basyari; Rifqi Rohmatulloh; Laelatul Nuroh (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study seeks to investigate students and their position and relationship with educators, as well as the noble character and ethics of students resulting from the actualization of noble values. All three are examined through the lens of Islamic education. Utilized is qualitative research conducted using a holistic-descriptive methodology. The data sources were retrieved from library records. At the level of data analysis, hermeneutic analysis is employed. The findings of this research Students are scientific subjects who cultivate their potential and form their personalities. The relationship between students and educators is not limited to knowledge partners constrained by the rules of educational institutions, but also includes partners in devotion to Allah SWT. Character is a personality shaped by the habitual realization of values through attitudes and deeds. The most admirable student personality is one shaped by attitudes and deeds that reflect divine values. The Prophet Muhammad SAW became a human prototype who taught the five divine values of faith, honesty, dependability, divine messengership, and intelligence. In the context of Islamic education in Indonesia, student ethics are absolutely predicated on five values: devotion to Allah SWT, prophethood, honor, knowledge practice, and democracy.